PELAKSANAAN MUTASI PEJABAT STRUKTURAL DI KANTOR BADAN KEPEGAWAIAN DAN DIKLAT DAERAH KABUPATEN POLEWALI MANDAR - S, Ibnu Khaldun; Setiawati, Budi; Burhanuddin, Burhanuddin (Universitas Muhammadiyah Makassar, 2022)
This research aimed to find out the implementation of promotion, implementation of rotation and the implementation of demotion. The kind of this research used qualitative research. Data collection techniques obtained by using observation, interviews, and documentation. The results of this study indicate that the implementation of the promotion was based on seniority, educational qualifications, work performance and loyalty, but there were several problems in its application. There are a number of things that are still lacking in the criteria of promotion such as, work time of employee is longer but they are not getting promotion and there are some employees who have educational qualifications that are less in line with their position. The implementation of rotation has been based on work ability, work attitude and working conditions, but most employees are rotated based on their wish to be rotated. This case is caused by dissatisfaction of employee with their workplace, so there are several employees who ask to be rotated, while the demotion is caused by a dysfunctional violation by the employee and an organizational reform that requires a descent in position. Based on the research there have never been employees who got demotion in Polewali Mandar Regency.